Orgelforschung in europäischem Geist. Die Orgellandschaften Rumäniens in Geschichte und Gegenwart am Beispiel der Temeswarer Orgelbaufirma Wegenstein - Franz METZ (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Organ research in European spirit. Romania’s organ landscapes in his-tory and present. The Timisoara organbuilding company Wegenstein.